2009
DOI: 10.1086/605954
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Tolerance in Anhydrobiotic Tardigrades Is Limited by Glass Transition

Abstract: Survival in microhabitats that experience extreme fluctuations in water availability and temperature requires special adaptations. To withstand such environmental conditions, tardigrades, as well as some nematodes and rotifers, enter a completely desiccated state known as anhydrobiosis. We examined the effects of high temperatures on fully desiccated (anhydrobiotic) tardigrades. Nine species from the classes Heterotardigrada and Eutardigrada were exposed to temperatures of up to 110 degrees C for 1 h. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 35 publications
9
105
0
4
Order By: Relevance
“…Fixation was followed by four 15 minute and one overnight wash in PB-Triton with 0.1% NaN 3 . Specimens were then incubated at room temperature for 27 hrs in a 1:40 dilution of phalloidin in PB-Triton with 0.1% NaN 3 . Following phalloidin incubation, specimens were rinsed three times for 5 minutes in PB-Triton.…”
Section: Phalloidin Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation was followed by four 15 minute and one overnight wash in PB-Triton with 0.1% NaN 3 . Specimens were then incubated at room temperature for 27 hrs in a 1:40 dilution of phalloidin in PB-Triton with 0.1% NaN 3 . Following phalloidin incubation, specimens were rinsed three times for 5 minutes in PB-Triton.…”
Section: Phalloidin Stainingmentioning
confidence: 99%
“…The taxon Tardigrada is composed of microscopic invertebrates known for their remarkable ability to survive hostile environments, including extremes in temperature, pressure, salinity, radiation, and even the vacuum of outer space [1][2][3][4][5][6][7][8]. Tardigrada is an ancient lineage, with a fossil record extending back to the Cambrian period [9].…”
Section: Introductionmentioning
confidence: 99%
“…it prevents lethal formation of intracellular ice crystals and provides molecular stability to macromolecules and cell structures. Recently, it was suggested that vitrification is an essential part of the survival strategy in anhydrobiotic invertebrates (30,31) and deeply supercooled arctic beetles (32).…”
Section: The Propensity Of Body Water To Undergo Glass Transition Incmentioning
confidence: 99%
“…asiaticum, but another species (reported as Milnesium tardigradum Doyère 1840 but probably also M. asiaticum or M. cf. asiaticum) has been reported to be more tolerant than R. coronifer to ultraviolet radiation, freezing, and high temperature Westh, 1992, 2001;Jöns-son et al, 2008;Hengherr et al, 2009aHengherr et al, , 2009b. Also differences in biochemistry connected with desiccation have been documented in these two species (Westh and Ramløv, 1991;Hengherr et al, 2008;Jönsson and Persson, 2010).…”
Section: Discussionmentioning
confidence: 99%